2002
DOI: 10.1016/s0092-8674(02)00822-x
|View full text |Cite
|
Sign up to set email alerts
|

Modifying Gene Expression Programs by Altering Core Promoter Chromatin Architecture

Abstract: Transcriptional activation of the IFN-beta gene in response to virus infection requires the assembly of an enhanceosome, which instructs a recruitment program of chromatin modifiers/remodelers and general transcription factors to the promoter. This program culminates with sliding of a nucleosome blocking the core promoter to a downstream position, a prerequisite for transcriptional activation. We show that delivery of this nucleosome to the same downstream position to create an accessible IFN-beta core promote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
134
0
11

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 172 publications
(152 citation statements)
references
References 32 publications
7
134
0
11
Order By: Relevance
“…Because studies of transcription factor function have largely been restricted to a select set of promoters identified by changes in gene expression, very little is known about transcription factors binding to regions without a direct transcriptional effect. It is well known that some genes are regulated by combinatorial action; general or tissue-specific factors contribute architectures conducive to the functions of an inducible protein (46,52,68). This leaves open the possibility of the inverse situation, where inducible transcription factors bind to any number of promoters lacking the accessory factors necessary for a transcriptional response.…”
Section: Discussionmentioning
confidence: 99%
“…Because studies of transcription factor function have largely been restricted to a select set of promoters identified by changes in gene expression, very little is known about transcription factors binding to regions without a direct transcriptional effect. It is well known that some genes are regulated by combinatorial action; general or tissue-specific factors contribute architectures conducive to the functions of an inducible protein (46,52,68). This leaves open the possibility of the inverse situation, where inducible transcription factors bind to any number of promoters lacking the accessory factors necessary for a transcriptional response.…”
Section: Discussionmentioning
confidence: 99%
“…Recently it has been shown that nucleosomes positioned across the transcriptional control regions of different genes, including IL-12p35 (61), IL-12p40 (62,63), IL-2 (64), IFN␤ (42,65), and HIV-1 long terminal repeat (66), are remodeled upon cell activation. Together with TNFSF6, these genes share a common low (or undetectable) basal transcription rate coupled to a high transcription rate in response to activating factors.…”
Section: Discussionmentioning
confidence: 99%
“…Fixed cells were used at a concentration of 2 ϫ 10 7 cells per experimental point. ChIP assays were performed as described (38). For each immunoprecipitation, 10 g of chromatin was used.…”
Section: Cd25mentioning
confidence: 99%